Straightening Identities in the Universal Enveloping Algebra of some Twisted Multiloop Algebras of sl4 - Chamberlin, Samuel Herron; Niraula, Jagrit (The PUMP Journal of Undergraduate Research, 2023)
We have formulated and proven some straightening identities in the universal enveloping algebras of the twisted multiloop algebras of sl4 with Chevalley involution twist. These formulas could be useful in investigating the representation theory of this algebra.